Tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film as well as preparation method and application thereof
By combining tannin acid with MXene and blending it with silver nanowires and aramid nanofibers, a modified titanium carbide/silver nanowires/aramid nanofiber electromagnetic shielding composite film was prepared, which solved the problem of MXene's easy oxidation and poor shielding durability, and achieved efficient, stable and high-temperature resistant electromagnetic shielding effect.
Patent Information
- Application Number
- CN202411843815.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-03-21
AI Technical Summary
When MXene is an electromagnetic shielding material, it is easy to oxidize, resulting in poor shielding durability.
By combining tannin acid with MXene to form a MXene-TA dispersion and blended with silver nanowires and aramid nanofibers, a tanninic acid modified titanium carbide/silver nanowires/aramimid nanofibers electromagnetic shielding composite film was prepared.
It effectively avoids the oxidation of MXene in the air, builds a dual conductive network with efficient electromagnetic shielding performance, improves the mechanical properties and long-term stability of the material, and obtains super-efficient, stable and high-temperature resistant electromagnetic shielding composite materials.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of development of conductive materials and electromagnetic shielding materials, and relates to a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film and a preparation method and application thereof. Background Art
[0002] With the rapid progress of ultra-large-scale integrated circuits, high-power electronic devices and highly integrated electronic devices, people's demand for high-speed operation of electronic devices has led to the development of electronic components in the direction of lightweight, miniaturization and integration. The electromagnetic radiation and electromagnetic interference generated by the operation of different electronic devices have penetrated into all aspects of national defense construction, national economy and people's lives, seriously affecting the normal operation of electronic equipment and the safe transmission of information. The electromagnetic pollution caused by this also directly endangers human health. In order to reduce or suppress the impact of electromagnetic radiation, researchers have conducted in-depth research and exploration in the field of electromagnetic interference (EMI) shielding. Although traditional metal materials have efficient electromagnetic interference shielding capabilities, their high density and poor flexibility limit their application in electromagnetic interference shielding.
[0003] Transition metal carbides and / or nitrides (MXenes) are a new type of two-dimensional (2D) nanomaterials with "metal-like" conductivity, large specific surface area, excellent mechanical properties and easy processing in aqueous dispersions derived from hydrophilic functional groups (-O, -OH, -F). Since MXene has all the basic properties required for efficient electromagnetic shielding materials, including excellent conductivity, light weight and large specific surface area, and most importantly, easy processing, MXene has great potential in the field of EMI shielding. Therefore, polymer composites prepared based on MXene have higher electromagnetic shielding performance. However, pure MXene is easily oxidized in water and oxygen environments, resulting in the failure of electromagnetic shielding performance in a short time. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film and a preparation method and application thereof, thereby solving the technical problems in the prior art that MXene is easily oxidized and has poor shielding durability when used as an electromagnetic shielding material.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film comprises the following steps: S1: adding titanium aluminum carbide powder to a mixed solution of lithium fluoride and hydrochloric acid, stirring for reaction, and ultrasonically treating to obtain a MXene aqueous dispersion; adding tannic acid to the MXene aqueous dispersion, stirring for reaction at room temperature to obtain a MXene-TA dispersion; dissolving potassium hydroxide and para-aramid chopped fibers in dimethyl sulfoxide, and stirring to obtain an aramid nanofiber dispersion; S2: The tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber.
[0006] Preferably, the potassium hydroxide and the para-aramid chopped fibers are dissolved in dimethyl sulfoxide, stirred for reaction, and then the aramid nanofibers are obtained. Specifically, the potassium hydroxide and the para-aramid chopped fibers are dissolved in dimethyl sulfoxide, stirred at 30-40°C for 3-4 hours, and then the aramid nanofibers are obtained. The diameter of the aramid nanofibers is 15-25 nm.
[0007] Preferably, the mass ratio of tannic acid to MXene is (1~2):1.
[0008] Preferably, the AgNWs have a diameter of 58-62 nm and a length of 20-60 μm.
[0009] Preferably, the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber, specifically: the MXene-TA dispersion, the aramid nanofiber and the AgNWs dispersion are blended and then vacuum filtered to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film.
[0010] Preferably, when the MXene-TA dispersion, aramid nanofibers and AgNWs dispersion are blended, the mass ratio of the total mass of the MXene-TA and AgNWs to the aramid nanofibers is (0.2~4):1; the mass ratio of the MXene-TA to the AgNWs is (10~1):(1~10).
[0011] Preferably, the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber, specifically: the aramid nanofiber is vacuum filtered once to obtain an aramid nanofiber layer; the MXene-TA dispersion and the AgNWs dispersion are mixed, and a second vacuum filtration is performed on the aramid nanofiber layer using a mixed dispersion of MXene-TA nanosheets and AgNWs to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film.
[0012] Preferably, when the MXene-TA dispersion and the AgNWs dispersion are mixed, the mass ratio of the MXene-TA to the AgNWs is (10~1):(1~10); the mass ratio of the total mass of the MXene-TA and the AgNWs to the mass of the aramid nanofibers is (0.2~4):1.
[0013] A tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film is prepared by the above method; the SE of the tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film T The value is 50~85 dB, the stress is 50~110 MPa, and the strain is 8~16%.
[0014] The application of the above-mentioned tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film in the field of electromagnetic shielding, Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a preparation method of a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film. In the method, tannic acid (TA) is used to modify MXene, thereby effectively avoiding the oxidation process of MXene in the air. In addition, MXene-TA is combined with AgNWs to build a double conductive network with high-efficiency electromagnetic shielding performance. Aramid nanofibers (ANFs) have strong intermolecular interactions due to hydrogen bonds, π-π stacking and van der Waals forces between molecular chains, so that the electromagnetic shielding material has excellent mechanical properties, high specific surface area and temperature resistance. In addition, the strong hydrogen bonding effect provided by polyhydroxy tannic acid and aramid nanofibers in the composite material enables the MXene-TA-based composite film to have ultra-high mechanical properties and long-term stability. Finally, tannic acid-modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film was prepared by MXene-TA, AgNWs and ANFs, which increased the dissipation path of electromagnetic waves in the material, improved its absorption loss inside the material, and reduced the reflection of electromagnetic waves on the surface of the material, thereby obtaining an ultra-strong, efficient, stable, and high-temperature resistant electromagnetic shielding composite material, expanding the application field of electromagnetic shielding materials.
[0015] Furthermore, the potassium hydroxide and the para-aramid chopped fibers are dissolved in dimethyl sulfoxide, stirred for reaction, and then the aramid nanofibers are obtained. Specifically, the potassium hydroxide and the para-aramid chopped fibers are dissolved in dimethyl sulfoxide, stirred at 30-40°C for 3-4 hours, and then the aramid nanofibers are obtained. The diameter of the aramid nanofibers is 15-25 nm, which can increase the specific surface area of the aramid nanofibers, thereby enhancing their mechanical properties.
[0016] Furthermore, the mass ratio of tannic acid to MXene is (1-2):1, which enables the composite film to achieve the best mechanical properties at a higher EMISE value.
[0017] Furthermore, the diameter of the AgNWs is 58-62 nm and the length is 20-60 μm, which can make the AgNWs have a better aspect ratio and facilitate the combination with other components.
[0018] Furthermore, the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding blended film is prepared using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber. Specifically, the MXene-TA dispersion, the aramid nanofiber and the AgNWs dispersion are blended and then vacuum filtered to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film. The blended composite film can have ultra-high electromagnetic shielding performance and mechanical properties. At the same time, the TA-modified MXene greatly increases the service life of the composite film.
[0019] Furthermore, when the MXene-TA dispersion, aramid nanofiber and AgNWs dispersion are blended, the mass ratio of the total mass of the MXene-TA and AgNWs to the mass of the aramid nanofiber is (0.2~4):1; the mass ratio of the MXene-TA and AgNWs is (10~1):(1~10), which can effectively combine the shielding components to promote the improvement of electromagnetic shielding performance.
[0020] Furthermore, the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding layered film is prepared using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber, specifically: the aramid nanofiber is vacuum filtered once to obtain an aramid nanofiber layer; the MXene-TA dispersion and the AgNWs dispersion are mixed, and a second vacuum filtration is performed on the aramid nanofiber layer using a mixed dispersion of MXene-TA nanosheets and AgNWs to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film, which can make the layered composite film have ultra-high electromagnetic shielding performance and mechanical properties, and the TA-modified MXene greatly increases the service life of the composite film.
[0021] Furthermore, when the MXene-TA and AgNWs dispersions are mixed, the mass ratio of the MXene-TA to the AgNWs is (10~1):(1~10); the mass ratio of the total mass of the MXene-TA and the AgNWs to the mass of the aramid nanofiber is (0.2~4):1, which can effectively combine the shielding components to promote the improvement of the electromagnetic shielding performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 XRD patterns of MXene and MXene-TA; Figure 2 SEM images of MXene and MXene-TA, where (a) is the surface SEM image of MXene, (b) is the surface SEM image of MXene-TA, (c) is the cross-sectional SEM image of MXene, and (d) is the cross-sectional SEM image of MXene-TA; Figure 3 The electromagnetic shielding performance (EMI SE) and power R and A comparison diagram of MXene and MXene-TA, where (a) is the electromagnetic shielding performance, and (b) is the power R and A comparison; Figure 4 SEM images of MXene-TA / AgNWs / ANF composite films with a blended structure, where (a) is the SEM image at 3k magnification, (b) is the SEM image at 10k magnification, and (c) is the SEM image at 20k magnification; Figure 5The SEM image of MXene-TA / AgNWs / ANF composite film with double-layer gradient structure; Figure 6 The mechanical properties of MXene-TA / AgNWs / ANF composite films prepared in different embodiments (Examples 1 to 6) are shown; Figure 7 EMI SE diagram of MXene-TA / AgNWs / ANF composite film with blended structure, where (a) is EMISE diagram and (b) is EMI SE diagram T Figure 2. (c) shows EMI SE A picture; Figure 8 EMI SE diagram of (MXene-TA / AgNWs) / ANF composite film with double-layer gradient structure, where (a) is the EMI SE diagram and (b) is the EMI SE diagram. T Figure 2. (c) shows EMI SE A picture; DETAILED DESCRIPTION In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0024] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0025] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0026] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0027] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0028] The invention discloses a method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film, comprising the following steps: S1: Add titanium aluminum carbide powder to a mixed solution of lithium fluoride and hydrochloric acid, stir for reaction, and then ultrasonically treat to obtain a MXene aqueous dispersion; add tannic acid to the MXene aqueous dispersion, stir for reaction at room temperature, the mass ratio of tannic acid to MXene is (1-2):1, and a MXene-TA dispersion is obtained; potassium hydroxide and para-aramid chopped fibers are dissolved in dimethyl sulfoxide, and stirred at 30-40°C for 3-4 h to obtain the aramid nanofiber dispersion; the diameter of the aramid nanofiber is 15-25 nm.
[0029] S2: The tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber.
[0030] The AgNWs have a diameter of 58-62 nm and a length of 20-60 μm.
[0031] The tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared by using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber, specifically: after the MXene-TA dispersion, the aramid nanofiber and the AgNWs dispersion are blended, vacuum filtration is performed to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film. When the MXene-TA dispersion, the aramid nanofiber and the AgNWs dispersion are blended, the mass ratio of the total mass of the MXene-TA and the AgNWs to the mass of the aramid nanofiber is (0.2~4):1; the mass ratio of the MXene-TA to the AgNWs is (10~1):(1~10).
[0032] In addition, the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared by using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber, and the method can also be: the aramid nanofiber is vacuum filtered once to obtain an aramid nanofiber layer; the MXene-TA dispersion and the AgNWs dispersion are mixed, and the mixed dispersion of MXene-TA nanosheets and AgNWs is vacuum filtered twice on the aramid nanofiber layer to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film. When the MXene-TA dispersion and the AgNWs dispersion are mixed, the mass ratio of the MXene-TA to the AgNWs is (10~1):(1~10); the mass ratio of the total mass of the MXene-TA and the AgNWs to the aramid nanofiber is (0.2~4):1.
[0033] The present invention also discloses a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film prepared by the above method, and the SE of the tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film is T The value is 50~85 dB, the stress is 50~110 MPa, and the strain is 8~16%.
[0034] The present invention provides a method for preparing a tannic acid-modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film with strong hydrogen bonding. The preparation method utilizes the rich hydroxyl groups and antioxidant capacity of tannic acid to prepare composite films of different structures by vacuum-assisted filtration. The blended structure gives the prepared composite film excellent stability and mechanical properties due to the super strong hydrogen bonding between MXene-TA, AgNWs, and ANF; the double-layer gradient structure gives the composite film excellent electromagnetic shielding performance, stability, and mechanical properties due to the excellent (MXene-TA / AgNWs) coherent conductive layer and rich hydrogen bonding. The specific process of the preparation method is: First, lithium fluoride (LiF) and titanium aluminum carbide (Ti3AlC2) with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution, and then stirred at 40 °C for 48 h to obtain an etched mixed solution, which was then centrifuged, washed and ultrasonically treated to obtain a MXene water suspension. Specifically: first add lithium fluoride to the hydrochloric acid solution, stir at room temperature for 15 min, then add Ti3AlC2 powder, and stir in a 40 ℃ oil bath for 48 h; after stirring, divide it into centrifuge tubes and centrifuge it multiple times (centrifugation conditions: 4500 r / min, 5 min), pour out the supernatant after each centrifugation, and add deionized water again until the pH of the suspension reaches neutral; thereafter, shake the above solution vigorously to make it even, crush the cells by ultrasound for 30 min, centrifuge at 3500 r / min for 60 min, take the supernatant, and obtain a stable and uniformly dispersed MXene water suspension.
[0035] Secondly, potassium hydroxide powder and para-aramid chopped fibers in a mass ratio of 1.5:1 were dissolved in a certain amount of dimethyl sulfoxide (DMSO), and a small amount of deionized water was added and stirred for 4 h to obtain a dark red aramid nanofiber solution, which was then dispersed using a deflaker, filtered through a 2800-mesh sieve, washed and filtered with deionized water for multiple times, and then redispersed in deionized water to obtain a uniformly dispersed aramid nanofiber aqueous dispersion. Specifically, 1.5 g of potassium hydroxide block was ground into potassium hydroxide powder, added to 500 mL of dimethyl sulfoxide, 1 g of para-aramid chopped fiber was added while stirring at room temperature, a small amount of deionized water was added, and then stirred at 40 °C for 4 h to obtain a dark red liquid; then deionized water 4 times the volume of the solution was added and stirred for 15 min, then it was broken up with a soymilk maker, stirred for another 30 min, the deionized water was filtered with a sample sieve, deionized water was added several times for repeated washing until the filtered deionized water was colorless and transparent, and then it was dispersed in a certain amount of deionized water and stirred for 1 h to obtain an ANF aqueous dispersion.
[0036] Next, a certain amount of polyvinyl pyrrolidone-K30 and polyvinyl pyrrolidone-K90 were mixed and dissolved, and a certain amount of FeCl3 and AgNO3 solution were added, and the reaction was carried out at 140°C, and then ethanol was added to terminate the reaction, and finally washed with deionized water to prepare AgNWs aqueous dispersion; The specific method is as follows: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 are dissolved in 110 mg ethylene glycol (EG), and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution is poured into the mixture, stirred for a while, and then the mixture is immediately transferred to a reactor preheated at 140 °C, and 15 mL, 60 mg / mL AgNO3 solution is added dropwise. When the mixture turns gray and has a filamentous texture, a large amount of ethanol is added to terminate the reaction. Finally, it is centrifuged with deionized water for several times (5000 r / min, 10 min) to prepare an AgNWs aqueous dispersion.
[0037] Again, MXene was modified by tannic acid to obtain MXene-TA suspension; Specifically: prepare the MXene suspension to a concentration of 5 mg / mL, add 200 mg of tannic acid to 40 mL of MXene suspension (mass ratio of 1:1), and react at room temperature for 12 h.
[0038] Finally, the (MXene-TA / AgNWs) / ANF composite films with blended and double-layer gradient structures were prepared by one-step vacuum-assisted filtration or layer-by-layer vacuum-assisted filtration. Specifically, in one-step vacuum-assisted filtration, a mixed solution of MXene-TA, AgNWs, and ANF is first prepared, and then filtered to obtain a MXene-TA / AgNWs / ANF composite film with a blended structure. In step-by-step vacuum-assisted filtration, a layer of aramid nanofibers is first deposited as the main mechanical support layer, and then a layer of MXene-TA / AgNWs is deposited as the main conductive shielding layer, and finally a (MXene-TA / AgNWs) / ANF composite film with a double-layer gradient structure is prepared.
[0039] The invention discloses a method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film. First, a MXene suspension is prepared by an in-situ etching method, an aramid nanofiber dispersion is obtained by a macroscopic aramid short fiber deprotonation and dissociation method, and a silver nanowire dispersion is prepared by a polyol method; then, a MXene-TA dispersion is prepared based on tannic acid modified MXene nanosheets; a MXene-TA / AgNWs / ANF composite film with a blended structure is prepared by a one-step vacuum assisted filtration method; and a (MXene-TA / AgNWs) / ANF composite film with a double-layer structure is obtained by layer-by-layer vacuum assisted filtration, using aramid nanofibers as a mechanical support layer and MXene-TA / AgNWs as a conductive shielding layer. The design method has the advantages of simplicity, high efficiency, low equipment requirements, wide application range and environmental friendliness, can effectively avoid some problems existing in traditional electromagnetic shielding composite films, and the prepared composite film has high potential application value in the fields of flexible wearables, thermal management, high temperature resistance, etc. Aramid nanofibers (ANFs) have been widely used in various reinforced polymer substrates due to their excellent mechanical properties and high specific surface area (mainly from strong interchain interactions (such as hydrogen bonds, π-π stacking and van der Waals forces). At the same time, the good temperature resistance of aramid nanofibers has broadened its practical application areas. Based on the disadvantage of MXene's easy oxidation, MXene is modified by antioxidant tannic acid (TA), and MXene-TA and AgNWs are used to build a double conductive network with high-efficiency electromagnetic shielding performance. Among them, the strong hydrogen bonding provided by polyhydroxy tannic acid and aramid nanofibers in the composite material makes the MXene-TA-based composite film have ultra-high mechanical properties and long-term stability. Finally, through blending and double-layer gradient structure design, the dissipation path of electromagnetic waves in the material is increased, its absorption loss inside the material is improved, and the reflection of electromagnetic waves on the surface of the material is reduced, thereby obtaining a super-strong, efficient, stable, and high-temperature resistant electromagnetic shielding composite material, which expands the application field of electromagnetic shielding materials.
[0040] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0041] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0042] Example 1 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0043] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0044] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0045] Preparation of MXene-TA / AgNWs / ANF composite film with blended structure: When using one-step vacuum-assisted filtration, a mixed solution of MXene-TA, AgNWs, and ANF is first prepared, and then a MXene-TA / AgNWs / ANF composite film with a blended structure is obtained after deposition and filtration. Among them, the mass ratio of the conductive material is MXene-TA:AgNWs=10:0, the total proportion of the two is 60%, and ANF accounts for 40%.
[0046] Example 2 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0047] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0048] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0049] Preparation of MXene-TA / AgNWs / ANF composite film with blended structure: When using one-step vacuum-assisted filtration, a mixed solution of MXene-TA, AgNWs, and ANF is first prepared, and then a MXene-TA / AgNWs / ANF composite film with a blended structure is obtained after deposition and filtration. Among them, the mass ratio of the conductive material is MXene-TA:AgNWs=9:1, with the total proportion of the two accounting for 60% and ANF accounting for 40%.
[0050] Example 3 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0051] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0052] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0053] Preparation of MXene-TA / AgNWs / ANF composite film with blended structure: When using one-step vacuum-assisted filtration, a mixed solution of MXene-TA, AgNWs, and ANF is first prepared, and then a MXene-TA / AgNWs / ANF composite film with a blended structure is obtained after deposition and filtration. Among them, the mass ratio of conductive materials is MXene-TA:AgNWs=7:3, with the total proportion of the two accounting for 60% and ANF accounting for 40%.
[0054] Example 4 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0055] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0056] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0057] Preparation of MXene-TA / AgNWs / ANF composite film with blended structure: When using one-step vacuum-assisted filtration, a mixed solution of MXene-TA, AgNWs, and ANF is first prepared, and then a MXene-TA / AgNWs / ANF composite film with a blended structure is obtained after deposition and filtration. Among them, the mass ratio of the conductive material is MXene-TA:AgNWs=5:5, with the total proportion of the two accounting for 60% and ANF accounting for 40%.
[0058] Example 5 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0059] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0060] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0061] Preparation of MXene-TA / AgNWs / ANF composite film with blended structure: When using one-step vacuum-assisted filtration, a mixed solution of MXene-TA, AgNWs, and ANF is first prepared, and then a MXene-TA / AgNWs / ANF composite film with a blended structure is obtained after deposition and filtration. Among them, the mass ratio of the conductive material is MXene-TA:AgNWs=3:7, with the total proportion of the two accounting for 60% and ANF accounting for 40%.
[0062] Example 6 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0063] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0064] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0065] Preparation of MXene-TA / AgNWs / ANF composite film with blended structure: When using one-step vacuum-assisted filtration, a mixed solution of MXene-TA, AgNWs, and ANF is first prepared, and then a MXene-TA / AgNWs / ANF composite film with a blended structure is obtained after deposition and filtration. Among them, the mass ratio of the conductive material is MXene-TA:AgNWs=1:9, the total proportion of the two is 60%, and ANF accounts for 40%.
[0066] Example 7 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0067] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0068] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0069] Preparation of double-layer gradient structure MXene-TA / AgNWs / ANF composite film: When using step-by-step vacuum assisted filtration, first deposit a layer of aramid nanofiber as the main mechanical support layer, and then deposit a layer of MXene-TA / AgNWs as the main conductive shielding layer, and finally prepare a (MXene-TA / AgNWs) / ANF composite film with a double-layer gradient structure. Among them, the mass ratio of conductive materials is MXene-TA:AgNWs=9:1, the total proportion of the two is 60%, and ANF accounts for 40%.
[0070] Example 8 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0071] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0072] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0073] Preparation of double-layer gradient structure MXene-TA / AgNWs / ANF composite film: When using step-by-step vacuum assisted filtration, first deposit a layer of aramid nanofiber as the main mechanical support layer, and then deposit a layer of MXene-TA / AgNWs as the main conductive shielding layer, and finally prepare a (MXene-TA / AgNWs) / ANF composite film with a double-layer gradient structure. Among them, the mass ratio of conductive materials is MXene-TA:AgNWs=7:3, the total proportion of the two is 60%, and ANF accounts for 40%.
[0074] Example 9 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0075] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0076] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0077] Preparation of double-layer gradient structure MXene-TA / AgNWs / ANF composite film: When using step-by-step vacuum assisted filtration, first deposit a layer of aramid nanofiber as the main mechanical support layer, and then deposit a layer of MXene-TA / AgNWs as the main conductive shielding layer, and finally prepare a (MXene-TA / AgNWs) / ANF composite film with a double-layer gradient structure. Among them, the mass ratio of conductive materials is MXene-TA:AgNWs=5:5, the total proportion of the two is 60%, and ANF accounts for 40%.
[0078] Example 10 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0079] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0080] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0081] Preparation of double-layer gradient structure MXene-TA / AgNWs / ANF composite film: When using step-by-step vacuum assisted filtration, first deposit a layer of aramid nanofiber as the main mechanical support layer, and then deposit a layer of MXene-TA / AgNWs as the main conductive shielding layer, and finally prepare a (MXene-TA / AgNWs) / ANF composite film with a double-layer gradient structure. Among them, the mass ratio of conductive materials is MXene-TA:AgNWs=3:7, the total proportion of the two is 60%, and ANF accounts for 40%.
[0082] Embodiment 11 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0083] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0084] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0085] Preparation of double-layer gradient structure MXene-TA / AgNWs / ANF composite film: When using step-by-step vacuum assisted filtration, first deposit a layer of aramid nanofiber as the main mechanical support layer, and then deposit a layer of MXene-TA / AgNWs as the main conductive shielding layer, and finally prepare a (MXene-TA / AgNWs) / ANF composite film with a double-layer gradient structure. Among them, the mass ratio of conductive materials is MXene-TA:AgNWs=1:9, the total proportion of the two is 60%, and ANF accounts for 40%.
[0086] Example 12 Preparation of MXene aqueous dispersion: Lithium fluoride and titanium aluminum carbide powder with a mass ratio of 1.6:1 were dissolved in a certain amount of hydrochloric acid (9 mol / L) solution. The specific steps were as follows: 8 g of lithium fluoride was added to 100 mL of hydrochloric acid (9 mol / mL) solution, stirred at room temperature for 15 min, 5 g of titanium aluminum carbide powder was added to the above mixed solution, stirred in a 40 ℃ oil bath for 48 h, washed several times by centrifugation in deionized water (4500 r / min, 5 min) until the pH of the suspension was neutral, the mixed solution was vigorously shaken by hand, the cells were crushed and ultrasonicated for 30 min, centrifuged for 60 min, and the supernatant was taken to obtain a uniformly dispersed MXene aqueous dispersion. 500 mg of tannic acid powder was added to 100 mL of MXene aqueous dispersion with a concentration of 5 mg / mL, and magnetically stirred at room temperature for a period of time to obtain a tannic acid-modified MXene dispersion (MXene-TA).
[0087] Preparation of aramid nanofiber aqueous dispersion: Grind 1.5 g of potassium hydroxide block into potassium hydroxide powder, add it to 500 mL of dimethyl sulfoxide, add 1 g of para-aramid chopped fibers while stirring at room temperature, then add a small amount of deionized water, stir at 40 °C for 4 h to obtain a dark red liquid; add deionized water 4 times the volume of the solution and stir for 15 min, then use a soymilk machine to break it up, stir for another 30 min, filter the deionized water with a sample sieve, add deionized water several times to wash repeatedly until the filtered deionized water becomes colorless and transparent, then disperse it in a certain amount of deionized water, stir for 1 h to obtain ANF aqueous dispersion.
[0088] Preparation of AgNWs aqueous dispersion: 0.25 g polyvinyl pyrrolidone-K30 and 0.50 g polyvinyl pyrrolidone-K90 were dissolved in 110 mg ethylene glycol (EG) and stirred vigorously at room temperature. Then, 12.5 mL FeCl3 solution was poured into the mixture and stirred for a while. Then, the mixture was immediately transferred to a reactor preheated at 140 °C and 15 mL of 60 mg / mL AgNO3 solution was added dropwise. When the mixture turned gray and had a filamentous texture, a large amount of ethanol was added to terminate the reaction. Finally, the mixture was centrifuged several times with deionized water (5000 r / min, 10 min) to prepare AgNWs aqueous dispersion.
[0089] Preparation of double-layer gradient structure MXene-TA / AgNWs / ANF composite film: When using step-by-step vacuum assisted filtration, first deposit a layer of aramid nanofiber as the main mechanical support layer, and then deposit a layer of MXene-TA / AgNWs as the main conductive shielding layer, and finally prepare a (MXene-TA / AgNWs) / ANF composite film with a double-layer gradient structure. Among them, the mass ratio of conductive materials is MXene-TA:AgNWs=10:0, the total proportion of the two is 60%, and ANF accounts for 40%.
[0090] Figure 1 Figure 2 is the XRD spectrum of MXene and MXene-TA. It can be seen from the figure that the strength of MXene-TA after modification is lower than that of MXene.
[0091] Figure 2 These are the SEM images of MXene and MXene-TA. It can be seen from the figure that TA-modified MXene has no obvious effect on the microstructure of pure MXene.
[0092] Figure 3 The electromagnetic shielding performance (EMI SE) and power R and A comparison diagram of MXene and MXene-TA, where (a) is the electromagnetic shielding performance and (b) is the power R and A comparison. It can be seen from the figure that TA-modified MXene has little effect on the electromagnetic shielding value of pure MXene and can be ignored; the A value of MXene-TA increases, and the absorption of electromagnetic waves increases; Figure 4 The SEM images of MXene-TA / AgNWs / ANF composite films with a blended structure; (a) is the SEM image at a magnification of 3k, (b) is the SEM image at a magnification of 10k, and (c) is the SEM image at a magnification of 20k. It can be seen from the figure that MXene-TA, AgNWs, and ANF in the composite film are uniformly dispersed; Figure 5 This is the SEM image of the MXene-TA / AgNWs / ANF composite film with a double-layer gradient structure. It can be seen from the figure that the upper layer is MXene-TA and AgNWs, and the lower layer is ANF; Figure 6 The mechanical properties of the MXene-TA / AgNWs / ANF composite films prepared in different embodiments (Examples 1 to 6) are shown in the figure. As can be seen from the figure, as the ratio of MXene-TA to AgNWs decreases (the content of MXene-TA increases), the mechanical properties of the composite film increase; Figure 7 EMI SE diagram of MXene-TA / AgNWs / ANF composite film with blended structure, where (a) is EMISE diagram and (b) is EMI SE diagram TFigure 2. (c) shows EMI SE A Figure; It can be seen from the figure that as the ratio of MXene-TA to AgNWs increases (AgNWs content increases), the electromagnetic shielding performance increases; Figure 8 EMI SE diagram of (MXene-TA / AgNWs) / ANF composite film with double-layer gradient structure, where (a) is the EMI SE diagram and (b) is the EMI SE diagram. T Figure 2. (c) shows EMI SE A Figure; It can be seen from the figure that as the ratio of MXene-TA to AgNWs increases (AgNWs content increases), the electromagnetic shielding performance increases.
[0093] Embodiment 13 A method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film comprises the following steps: S1: Add titanium aluminum carbide powder to a mixed solution of lithium fluoride and hydrochloric acid, stir for reaction, and then ultrasonically treat to obtain a MXene aqueous dispersion; add tannic acid to the MXene aqueous dispersion, stir for reaction at room temperature, the mass ratio of tannic acid to MXene is 1:1, and a MXene-TA dispersion is obtained; dissolve potassium hydroxide and para-aramid chopped fibers in dimethyl sulfoxide, stir for 4 h at 30°C, and obtain the aramid nanofiber dispersion; the diameter of the aramid nanofiber is 15 nm.
[0094] S2: The tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared by using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber. The AgNWs have a diameter of 58 nm and a length of 20 μm.
[0095] The tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared by using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber, specifically: after the MXene-TA dispersion, the aramid nanofiber and the AgNWs dispersion are blended, vacuum filtration is performed to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film. When the MXene-TA dispersion, the aramid nanofiber and the AgNWs dispersion are blended, the total mass ratio of the MXene-TA and AgNWs to the mass ratio of the aramid nanofiber is 1.5:1; the mass ratio of the MXene-TA to the AgNWs is 10:1.
[0096] The SE of a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film prepared in this embodiment TThe value is 50 dB, the stress is 50 MPa, and the strain is 8%.
[0097] Embodiment 14 A method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film comprises the following steps: S1: Add titanium aluminum carbide powder to a mixed solution of lithium fluoride and hydrochloric acid, stir for reaction, and then ultrasonically treat to obtain a MXene aqueous dispersion; add tannic acid to the MXene aqueous dispersion, stir for reaction at room temperature, the mass ratio of tannic acid to MXene is 2:1, and a MXene-TA dispersion is obtained; dissolve potassium hydroxide and para-aramid chopped fibers in dimethyl sulfoxide, stir for 3 h at 40°C, and obtain the aramid nanofiber dispersion; the diameter of the aramid nanofiber is 25 nm.
[0098] S2: The aramid nanofiber is subjected to a vacuum filtration to obtain an aramid nanofiber layer; the MXene-TA dispersion and the AgNWs dispersion are mixed, and the mixed dispersion of MXene-TA nanosheets and AgNWs is subjected to a second vacuum filtration on the aramid nanofiber layer to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film. When the MXene-TA dispersion and the AgNWs dispersion are mixed, the mass ratio of the MXene-TA to the AgNWs is 1:10; the mass ratio of the total mass of the MXene-TA and the AgNWs to the aramid nanofiber is 1.5:1.
[0099] The present invention also discloses a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film prepared by the above method, and the SE of the tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film is T The value is 85 dB, the stress is 110 MPa, and the strain is 16%.
[0100] Embodiment 15 A method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film comprises the following steps: S1: Add titanium aluminum carbide powder to a mixed solution of lithium fluoride and hydrochloric acid, stir for reaction, and then ultrasonically treat to obtain a MXene aqueous dispersion; add tannic acid to the MXene aqueous dispersion, stir for reaction at room temperature, the mass ratio of tannic acid to MXene is 1.5:1, and a MXene-TA dispersion is obtained; potassium hydroxide and para-aramid chopped fibers are dissolved in dimethyl sulfoxide, and stirred at 35°C for 3.5 hours to obtain the aramid nanofiber dispersion; the diameter of the aramid nanofiber is 20 nm.
[0101] S2: The aramid nanofiber is vacuum filtered once to obtain an aramid nanofiber layer; the MXene-TA dispersion and the AgNWs dispersion are mixed, and the mixed dispersion of MXene-TA nanosheets and AgNWs is vacuum filtered twice on the aramid nanofiber layer to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film. When the MXene-TA dispersion and the AgNWs dispersion are mixed, the mass ratio of the MXene-TA to the AgNWs is 5:5; the total mass ratio of the MXene-TA and the AgNWs to the mass ratio of the aramid nanofiber is 1.5:1. The diameter of the AgNWs is 60 nm and the length is 40 μm.
[0102] The SE of a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film prepared in this embodiment T The value is 70 dB, the stress is 70 MPa, and the strain is 9.5%.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film, characterized in that: The following steps are involved: S1: adding titanium aluminum carbide powder to a mixed solution of lithium fluoride and hydrochloric acid, stirring for reaction, and ultrasonically treating to obtain a MXene aqueous dispersion; adding tannic acid to the MXene aqueous dispersion, stirring for reaction at room temperature to obtain a MXene-TA dispersion; dissolving potassium hydroxide and para-aramid chopped fibers in dimethyl sulfoxide, and stirring to obtain an aramid nanofiber dispersion; S2: The MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber are used to prepare the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film.
2. The method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film according to claim 1, characterized in that: The potassium hydroxide and the para-aramid chopped fibers are dissolved in dimethyl sulfoxide, stirred for reaction, and then the aramid nanofibers are obtained. Specifically, the potassium hydroxide and the para-aramid chopped fibers are dissolved in dimethyl sulfoxide, stirred for 3 to 4 hours at 30 to 40° C., and then the aramid nanofibers are obtained. The diameter of the aramid nanofibers is 15 to 25 nm.
3. The method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film according to claim 1, characterized in that: The mass ratio of tannic acid to MXene is (1~2):
1.
4. The method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film according to claim 1, characterized in that: The AgNWs have a diameter of 58-62 nm and a length of 20-60 μm.
5. The method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film according to claim 1, characterized in that: The tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared by using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber, specifically: the MXene-TA dispersion, the aramid nanofiber and the AgNWs dispersion are blended and then vacuum filtered to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film.
6. The method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film according to claim 5, characterized in that: When the MXene-TA dispersion, aramid nanofibers and AgNWs dispersion are blended, the mass ratio of the total mass of the MXene-TA and AgNWs to the aramid nanofibers is (0.2~4):1; the mass ratio of the MXene-TA to the AgNWs is (10~1):(1~10).
7. The method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film according to claim 1, characterized in that: The tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film is prepared by using the MXene-TA dispersion, the AgNWs dispersion and the aramid nanofiber, specifically: the aramid nanofiber is vacuum filtered once to obtain an aramid nanofiber layer; the MXene-TA dispersion and the AgNWs dispersion are mixed, and a mixed dispersion of MXene-TA nanosheets and AgNWs is vacuum filtered twice on the aramid nanofiber layer to obtain the tannic acid modified titanium carbide / silver nanowire composite electromagnetic shielding composite film.
8. The method for preparing a tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film according to claim 7, characterized in that: When the MXene-TA dispersion and the AgNWs dispersion are mixed, the mass ratio of the MXene-TA to the AgNWs is (10~1):(1~10); the mass ratio of the total mass of the MXene-TA and the AgNWs to the mass of the aramid nanofibers is (0.2~4):
1.
9. A tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film, characterized in that: Prepared by the method described in any one of claims 1 to 8; the SE of the tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film T The value is 50~85 dB, the stress is 50~110 MPa, and the strain is 8~16%.
10. Use of the tannic acid modified titanium carbide / silver nanowire / aramid nanofiber electromagnetic shielding composite film as described in claim 9 in the field of electromagnetic shielding.
Citation Information
Patent Citations
Flexible high-strength MXene-based electromagnetic shielding composite film and preparation method thereof
CN111809439A
Preparation method of CNF / MXene-silver nanowire composite film
CN113004556A
Flexible aramid nanofiber and silver nanowire composite electromagnetic shielding thin film material and preparation method thereof
CN113999524A
Porous hollow MXene / aramid nanofiber electromagnetic shielding composite film as well as preparation method and application thereof
CN117645735A
ANF / MMT-MXene electromagnetic shielding paper and preparation method thereof
CN117986648A
Cited By
Self-supporting flexible silver-rich electrode and preparation method and application thereof
CN120341293A
A self-supporting flexible silver-rich electrode and its preparation method and application
CN120341293B